Obesogenic environment - intervention opportunities - Mauro Fisberg; Priscila Maximino; Juliana Kain; Irina Kovalskys (Elsevier, 2016)
ABSTRACT Objectives: To evaluate environmental obesogenic-related factors, such as physical activity in neighborhoods and schools, nutritional behavior, and intervention programs. Sources: Critical analysis of literature with personal point of view from infant obesity experts and political advisors for public intervention. Data synthesis: Although obesity is a public health problem affecting several age groups, it is among children and adolescents that it plays a more important role, due to treatment complexity, high likelihood of persistence into adulthood, and association with other non- transmissible diseases while still in early age. Environment is a main component of the genesis and outcomes in the near future or long term. Modification of intake with high-density food, meal skipping, and high intake of saturated fat, sugar, and salt, associated to high levels of sedentarism are main causes of obesity. Conclusion: Intervention opportunities are related to modifications in political, environmental, and individual settings. School and physical activities in the educational environment are intertwined with nutrition intervention in continuous education. A critical review of some different scenarios in Latin American countries is presented.